FENCES BOOKING SYSTEM ON TRUE CV.PRIMA WITH MICROSOFT VISUAL BASIC 6.0 - Koesdwiyanto Wibowo; Rahayu Noveandini SKom, MMSi Rahayu Noveandini SKom, MMSi (Jurnal Sistem Informasi, 2006)
The development of increasingly sophisticated computer that is very helpful in dataprocessing still using manual systems. This often raises issues related to the accuracyof the data which resulted in delays in data processing.Valuable information is the information quickly and accurately. Then needed acomputerized system as a supporter. Rail reservation system in CV. Prima Sejatidesigned with the aim to obtain and process information quickly and accurately aswell as secure data storage. So with the end result is useful in decision making.